FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA (STUDI KASUS MAHASISWA FAKULTAS EKONOMI DAN BISNIS UHO) - Afrizal Afrizal; Muh Rafiy; Ambo Wonua Nusantara (Universitas Halu Oleo, 2018)
This study aims to identify factors Revenue Expectations, environmental factors and factor values of entrepreneurship Influential Entrepreneur of Interest on Student Faculty of Economics and Business UHO. The sampling technique used in this research is census that took the entire population of the research samples, commonly called a saturated sample. After the census of 2014 class of 725 students obtained many as 28 students have already berwirabusiness. So that the number of samples in this study were 28 people, the analysis of data using qualitative descriptive that was obtained through interviews and questionnaires. The results showed that in terms of income expectation factors it can be seen that students are very interested in entrepreneurship, because proven by the majority of respondents’ answers stated that the desire for entrepreneurship is influenced by the desire to earn high income with a percentage of 82.14 percent .in terms of environmental factors it can be seen that students who are dominant entrepreneurs are influenced by environmental factors of the community with a percentage of 78.57 percent and from the aspect of entrepreneurial values, it can be seen that students can be categorized as very interested in entrepreneurship, because it is proven by the majority of respondents answers that they have a motive of achievement with percentage of 96.43 percent.